1984
DOI: 10.1159/000137993
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of Enalapril in Acute Myocardial Ischemia

Abstract: Enalapril, a new potent orally active angiotensin-converting enzyme inhibitor, was studied in cats subjected to acute myocardial ischemia. Enalapril, administered intravenously (2 mg/kg, plus 2 mg/kg/h) 30 min after ligation of the left coronary artery, significantly reduced the pressure-rate index, an indicator of myocardial oxygen demand. This was confirmed in isolated cat papillary muscles where enalapril reduced contractile force by 5–10%. During myocardial ischemia, enalapril reversed the elevated S-T seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…It is well established that both H 2 S and NO exert potent cytoprotective effects in the setting of cardiovascular disease in various animal model systems (5,7,(13)(14)(15). In addition, H 2 S has been reported to be cytoprotective in some organ systems, such as the central nervous system and gastrointestinal tract, independent of NO (3,11,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that both H 2 S and NO exert potent cytoprotective effects in the setting of cardiovascular disease in various animal model systems (5,7,(13)(14)(15). In addition, H 2 S has been reported to be cytoprotective in some organ systems, such as the central nervous system and gastrointestinal tract, independent of NO (3,11,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that blockade of the renin-angiotensin system by captopril (Ertl et al, 1982), enalapril (Lefer & Peck, 1984;Hock et al, 1985), and ramipril (Martorana et al, 1990) produces a beneficial effect in myocardial ischaemia. However, this cardioprotective effect of angiotensin Iconverting enzyme inhibitors (ACEIs) is not universally recognized, as Liang et al (1982) and Daniell et al (1984) have failed to demonstrate any myocardial protection with ACEIs.…”
Section: Introductionmentioning
confidence: 99%
“…However, several experiments suggest that the anti-ischaemic effect of the sulphydryl-containing ACEI captopril could be due to non specific effects of this drug, such as an inhibition of oxygen free radical-dependent reperfusion injury (Westlin & Mullane, 1988;Chopra et al, 1992) and/or an interference with arachidonic acid metabolism (Van Gilst et al, 1987). However, in some experimental models of ischaemia, acute administration of non sulphydryl-containing ACEIs also limited infarct size in rats (Hock et al, 1985) and in cats (Lefer & Peck, 1984). Differences in animal models, duration and severity of ischaemia, occurrence of reperfusion, and drug concentrations could contribute to these conflicting results.…”
mentioning
confidence: 99%
“…Enalaprilat is an antagonist of angiotensin II in isolated coronary arteries [44] and antagonizes the coronary vasoconstrictor effect of angiotensin II [45]. It has been shown [18,19] that the renin-angiotensin system can be abruptly and completely blocked by an intravenous bolus injection of enalaprilat with a rapid improvement of cardiac performance in patients with chronic heart failure, achieving the peak effect within 30 min.…”
Section: Discussionmentioning
confidence: 99%